Kontribusi Perilaku Generasi Z terhadap Transformasi Kegiatan Ekonomi di Era Digitalisasi - Lhya Himong; Serilus Embu Rae; Angga Tobu; Yohanis Pemandi Lian (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid expansion of digital technology has reshaped how individuals interact, work, and participate in economic activities, with Generation Z positioned at the center of this transformation. Growing up in a fully digital environment, this generation demonstrates distinctive behavioral patterns that influence shifts in consumption, entrepreneurship, and digital work practices. This study aims to explain how Generation Z contributes to the transformation of economic activities in the digital era and to identify the challenges they encounter. Using a descriptive qualitative approach supported by questionnaires distributed to 100 respondents and a review of relevant literature, this study examines their digital consumption behavior, use of online platforms for entrepreneurship, and engagement in technology-based economic opportunities. The findings show that Generation Z plays a significant role in driving the modernization of economic activities through the intensive use of e-commerce, digital payments, fintech services, and creative activities on social media. They increasingly engage in content creation, online selling, and personal branding as alternative economic pathways. However, the study also highlights several challenges, including uneven advanced digital literacy, impulsive online spending, mental health pressures associated with constant digital exposure, and the need for continuous skill adaptation in response to automation and artificial intelligence. These findings emphasize the importance of strengthening digital literacy, entrepreneurship skills, financial awareness, and mental well-being to support their sustainable contribution to the digital economy.